Metal organic framework synthesis in the presence of surfactants: towards hierarchical MOFs?1. Issue 7 (21st February 2015) - Seoane, B.; Dikhtiarenko, A.; Mayoral, A.; Tellez, C.; Coronas, J.; Kapteijn, F.; Gascon, J.
<x xml:space="preserve">Abstract</x> We report the effect of synthesis parameters on the textural properties of Al based MOFs synthesized in the presence CTAB.